2020
DOI: 10.1002/eng2.12119
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and prediction of surface roughness using multiple regressions: A noncontact approach

Abstract: In the present work, a machine vision system is introduced, which captures images and extracts surface texture features of machined surfaces. The texture feature parameters are extracted using the gray‐level co‐occurrence matrix and correlated with different surface roughness parameters recorded by a contact‐type surface profilometer. The image acquisition carried out at different roughness levels in order to extract texture features. The variation between each texture features and surface roughness parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Patel et al [174] explicitly showed that a vision strategy for the machine can be applied to test the ma-chined surface roughness. The fitness of experimental measurements is measured by multiple regression analyses.…”
Section: Surface Characteristics Measurement Using Machine Vision Tec...mentioning
confidence: 99%
“…Patel et al [174] explicitly showed that a vision strategy for the machine can be applied to test the ma-chined surface roughness. The fitness of experimental measurements is measured by multiple regression analyses.…”
Section: Surface Characteristics Measurement Using Machine Vision Tec...mentioning
confidence: 99%
“…In this stylus, a small conical diamond tip is touched and across the along surface of the specimen, while its deflection is recorded, the reading appears on the device's screen which represents the roughness value of the specimen in the micrometer unit (Ra in μm). [13]. Three randomly selected locations on the specimen surface was operated by a stylus to record the desired measurement of roughness values [14].…”
Section: Surface Roughness Testingmentioning
confidence: 99%
“…A machine vision system is offered, which captures images and extracts surface texture features of machined detail's surface [10]. The texture parameters are extracted, using the gray-level co-occurrence spacial matrix and correlated with different surface roughness parameters recorded by a contact-type profilometer.…”
Section: Problem's Statementmentioning
confidence: 99%